1998
DOI: 10.1038/34402
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between nitric oxide and haemoglobin under physiological conditions

Abstract: The tenet of high-affinity nitric oxide (NO) binding to a haemoglobin (Hb) has shaped our view of haem proteins and of small diffusible signaling molecules. Specifically, NO binds rapidly to haem iron in Hb (k approximately 10[7] M[-1] s[-1]) and once bound, the NO activity is largely irretrievable (Kd approximately 10[-5] s[-1]); the binding is purportedly so tight as to be unaffected by O2 or CO. However, these general principles do not consider the allosteric state of Hb or the nature of the allosteric effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
393
4
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(420 citation statements)
references
References 25 publications
16
393
4
2
Order By: Relevance
“…Indeed, several proteins involved in Ca 2+ and redox signaling are known to be modified by S-nitrosation, including L-type Ca 2+ channels [77], ryanodine receptors [78], thioredoxin [79] hemoglobin [80], mitochondrial K + ATP channels [81,82], TRP channels [83], and caspases [26]. The relative importance of complex I as a mediator of the cardioprotective effects of NO • remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several proteins involved in Ca 2+ and redox signaling are known to be modified by S-nitrosation, including L-type Ca 2+ channels [77], ryanodine receptors [78], thioredoxin [79] hemoglobin [80], mitochondrial K + ATP channels [81,82], TRP channels [83], and caspases [26]. The relative importance of complex I as a mediator of the cardioprotective effects of NO • remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin is also thought to be involved in the protection of cells against nitrosative stress [15;16]. Recent studies have shown that hemoglobin can bind and release NO as a redox reaction, thus functioning in close resemblance to cytochromes [17]. Neuroglobin and cytoglobin, two other members of the vertebrate globin family, also have protective functions including oxygen sensing and scavenging [9;13;14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Stamler and colleagues (6)(7)(8) suggests that NO binding to hemoglobin may play a role in the regulation of vascular tone, with NO binding and release tied to oxygen-induced allosteric structural transitions. In the lungs, hemoglobin is highly saturated with oxygen, and NO produced in the lungs is thought to bind to cysteine 93 on the β chain.…”
Section: Discussionmentioning
confidence: 99%